Self-worth and bonding emotions are related to well-being in health-care providers: a cross-sectional study - Weilenmann, S; Schnyder, U; Keller, N; Corda, C; Spiller, T; Brugger, F; Parkinson, B; von Kanel, R; Pfalz, M (BioMed Central, 2021)
Background: Interacting with patients can elicit a myriad of emotions in health-care providers. This may result in satisfaction or put providers at risk for stress-related conditions such as burnout. The present study attempted to identify emotions that promote provider well-being. Following eudaimonic models of well-being, we tested whether certain types of emotions that reflect fulfilment of basic needs (self-worth, bonding with patients) rather than positive emotions in general (as suggested by hedonic models) are linked to well-being. Specifically, we hypothesized that well-being is associated with positive emotions directed at the self, which reflect self-worth, and positive as well as negative emotions (e.g., worry) directed at the patient, which reflect bonding. However, we expected positive emotions directed at an object/situation (e.g., curiosity for a treatment) to be unrelated to well-being, because they do not reflect fulfilment of basic needs. Methods: 58 physicians, nurses, and psychotherapists participated in the study. First, in qualitative interviews, they reported their emotions directed at the self, the patient, or an object/situation during distressing interactions with patients. These emotions were categorised into positive emotions directed towards the self, the patient, and an object/situation, and negative emotions directed towards the patient that reflect bonding. Second, providers completed questionnaires to assess their hedonic and eudaimonic well-being. The well-being scores of providers who did and did not experience these emotions were compared. Results: Providers who experienced positive emotions directed towards the self or the patient had higher well-being than those who did not. Moreover, for the first time, we found evidence for higher well-being in providers reporting negative patient-directed emotions during distressing interactions. There was no difference between providers who did and did not experience positive object/situation-directed emotions. Conclusions: These findings may point towards the importance of “eudaimonic” emotions rather than just positive emotions in interactions with patients. Emotions such as contentment with oneself, joy for the patient’s improvement, and, notably, grief or worry for the patient may build a sense of self-worth and strengthen bonding with the patient. This may explain their association with provider well-being.